2020
DOI: 10.14710/jtsiskom.2020.13877
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the peak Covid-19 pandemic in Indonesia using SIR model

Abstract: This research implements the Susceptible, Infected, and Removed (SIR) model to predict the Covid-19 outbreak in Indonesia. The government official data, consisting of infected, dead, and recovered, are used as actual data to interpolate the model through matching data with minimum mean squared error (MSE). The study uses one of the Quasi-Newton search methods, the Broyden, Fletcher, Goldfarb, and Shanno (BFGS) algorithm, to determine the interaction coefficient's optimal value in the model with the minimum MSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…Model epidemiologi SIR dibagi menjadi tiga kompartemen, yaitu kelompok individu yang rentan penyakit (susceptible), kelompok individu yang terinfeksi (infected), kelompok individu yang telah sembuh dan kebal dari penyakit (recovered) [7]. Walaupun SIR memiliki bentuk model yang sederhana, model SIR dinilai paling sesuai untuk prediksi berbasis data dibandingkan dengan model lainnya yang lebih kompleks [8].…”
Section: Pendahuluan Perangkat Pandemi Corona Virus Disease 2019 (Cov...unclassified
“…Model epidemiologi SIR dibagi menjadi tiga kompartemen, yaitu kelompok individu yang rentan penyakit (susceptible), kelompok individu yang terinfeksi (infected), kelompok individu yang telah sembuh dan kebal dari penyakit (recovered) [7]. Walaupun SIR memiliki bentuk model yang sederhana, model SIR dinilai paling sesuai untuk prediksi berbasis data dibandingkan dengan model lainnya yang lebih kompleks [8].…”
Section: Pendahuluan Perangkat Pandemi Corona Virus Disease 2019 (Cov...unclassified
“…The fuzzy model for controlling hydroponic cultivation has been implemented by [3,4]. Whether the DFT system controlled its water pH was developed by [5] by using the Internet of Things system. [6] was developed as a hydroponic tower with a nutrient control system.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, setting constant rates of transmission and recovery results in a high number of projected infected cases once the model is applied to a vast and highly populated community; this could be at the scale of entire nations [ 12 ]. According to recent studies, SIR-based predictions using early data for COVID-19 cases have shown an enormous figure for predicted cases, with the peak reaching up to 15–30% of the total population [ 13 , 14 ]. Nevertheless, an absence of the psychological behavior of the population could overestimate the prediction figure [ 15 ].…”
Section: Introductionmentioning
confidence: 99%